Present Value Models and the Multi-Asset Problem: Comment. - Curley, Anthony J.; Carpenter, Charles G. (The Accounting Review, 1974)
Abstract This article presents comments on the article "Present Value Models and the Multi-Asset Problem," by Richard P. Brief and Joel Owen, published in the October 1973 issue of the journal "The Accounting Review." The relevance and adequacy of the internal rate of return model (IRR) is a topic of controversy in financial accounting. Brief and Owen examined the multi-asset dimension of the IRR issue, concluding that IRR is a firm model as contrasted to a single-asset model. Strictly interpreted, this conclusion would serve to render the IRR model useless, since it implies constancy of rate of return for any firm over time. The IRR model is often demonstrated arithmetically, but there is an advantage in analyzing the, model algebraically. When return on investment is realized over a number of periods, the geometric mean may be used to represent average periodic rate of return. If the reinvestment pattern is changed and a future value of $399.30 still results, the geometric mean continues to be 10%, but the internal rate of return is replaced by variable periodic rates of return. If the future value is changed, mean return will no longer be 10%. To calculate combined rate of return, reinvestment patterns must be assumed and the firm should then be considered in the context of a portfolio of assets.